Efeitos da eletrolipólise no perfil lipídico, glicêmico e hormonal de mulheres obesas - Paula, Mariana Ribeiro de (2013)
Obesity is characterized by the excessive accumulation of body fat. When the Body Mass Index (BMI) is higher than 30 kg/m², metabolic complications begin to appear. In Brazil, it is estimated that 40% of the population is above normal weight level, which increases the possibility of developing cardiovascular diseases. Obesity, especially in the abdominal region, is the result of a series of biochemical reactions that can lead to the development of Insulin Resistance (IR), type 2 diabetes, dyslipidemia (alterations in cholesterol), and atherosclerosis. Electrolipolysis is a technique for reducing adipose tissue. Pairs of acupuncture needles are inserted in the subcutaneous tissue and connected to an apparatus that generates low frequency electric current. The electrical stimulation induces physical alterations in the fat cells, including an increase in cellular metabolism and increased blood circulation. The aim of this study was to evaluate the effects of electrolipolysis on lipidic, glycemic and hormonal profiles of obese women. The sample was composed of 16 women with a BMI of over 30 kg/m² who had a sedentary lifestyle. They were submitted for 10 sessions of electrolipolysis at frequencies of 5-50 Hz during 40 minutes, three times a week. The statistic was verified using the Wilcoxon test, with an accepted significance level of p<0,05. The results were evaluated through anthropometric measurements and blood tests carried out in a clinical analysis laboratory. After the 10 sessions, the volunteers showed a significant reduction of 2% in their abdominal perimeters, 3% in terms of waist circumference and 4% in their waist-hip ratio (WHR). There was a significant increase of 4% in total cholesterol. In spite of this, the LDL-c, HDL-c, triglycerides, insulin, glycemia and C-reactive protein showed no significant increase. Therefore, it can be concluded that electrolipolysis is an effective technique in the treatment of fat, showing a significant reduction in the abdominal perimeter, which is an important factor for reducing the risk of developing chronic diseases. Nevertheless, the metabolic effects have yet to be clarified. The population of the sample in this study corresponds to the reality of patients who seek treatment to reduce fat at medical centers and esthetic clinics. The increase in total cholesterol requires further investigation, as it can be harmful to a patient’s health and this information is relevant in terms of public health services. The lipolytic effect triggered by electrolipolysis may have increased serum concentrations, fatty acids and glycerol, contributing to increased hepatic synthesis of cholesterol. It may be happened that the 4 week study was not sufficient for the use of fat as source of energy by the population.